Intermittent rivers and ephemeral streams ecology and management - Datry, Thibault 1977-; Bonada, Núria; Boulton, Andrew J. (London Academic Press, 2017)
Intermittent Rivers and Ephemeral Streams: Ecology and Management takes an internationally broad approach, seeking to compare and contrast findings across multiple continents, climates, flow regimes, and land uses to provide a complete and integrated perspective on the ecology of these ecosystems. Coupled with this, users will find a discussion of management approaches applicable in different regions that are illustrated with relevant case studies. In a readable and technically accurate style, the book utilizes logically framed chapters authored by experts in the field, allowing managers and policymakers to readily grasp ecological concepts and their application to specific situations.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Stream ecology; Electronic books